2013
DOI: 10.3389/fpsyt.2013.00077
|View full text |Cite
|
Sign up to set email alerts
|

Addiction: Choice or Compulsion?

Abstract: Normative thinking about addiction has traditionally been divided between, on the one hand, a medical model which sees addiction as a disease characterized by compulsive and relapsing drug use over which the addict has little or no control and, on the other, a moral model which sees addiction as a choice characterized by voluntary behavior under the control of the addict. Proponents of the former appeal to evidence showing that regular consumption of drugs causes persistent changes in the brain structures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 50 publications
2
52
0
2
Order By: Relevance
“…Further research could also evaluate potential predictors of dropout infrequently reported and therefore not assessed in the current meta‐analytic review. For example, with regard to participant characteristics, greater ambivalence toward treatment may be associated with higher rates of dropout . With regard to facilitator characteristics, stronger therapeutic alliance may predict a reduced likelihood of dropout , and with regard to treatment characteristics, psychosocial interventions that elicit feedback from participants/clients may produce lower dropout rates , as may those that engage in directed interventions designed to minimize this outcome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Further research could also evaluate potential predictors of dropout infrequently reported and therefore not assessed in the current meta‐analytic review. For example, with regard to participant characteristics, greater ambivalence toward treatment may be associated with higher rates of dropout . With regard to facilitator characteristics, stronger therapeutic alliance may predict a reduced likelihood of dropout , and with regard to treatment characteristics, psychosocial interventions that elicit feedback from participants/clients may produce lower dropout rates , as may those that engage in directed interventions designed to minimize this outcome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the belief among healthcare professionals that a patient can control injecting drug use was associated with more negative attitudes towards such patients [10]. Studies indicate that perceptions of addiction vary widely among health professionals [1113]. For example, some consider addiction as a chronic brain disease, resulting from genetic vulnerabilities and a change in brain function as a consequence of drug use [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Society has indeed struggled to acknowledge the pathology underlying problematic substance use and this has had implications for how the individuals affected have been treated (9). Traditionally, normative thinking about dependence has been divided between moral-, social-and medical models (10). Moral theories imply that individuals make a conscious choice to abuse substances and they should thus be held accountable for their problems.…”
Section: Failing Moral or A Real Disease?mentioning
confidence: 99%
“…Social theories highlight the influence of disruptive social factors such as unemployment and poverty to explain development and maintenance of substance use. The medical (or disease) model on the other hand, sees substance dependence as a neurobiological disease characterized by compulsive and relapsing substance use over which the individual has limited control (10). Over the past decades a biopsychosocial framework has become influential as an alternative to the dominant medical model (11).…”
Section: Failing Moral or A Real Disease?mentioning
confidence: 99%